1961
DOI: 10.3181/00379727-108-27013
|View full text |Cite
|
Sign up to set email alerts
|

Hemadsorption in Monkey Kidney Cell Cultures of Mycoplasma (PPLO) Recovered from Rats.

Abstract: difference between the 2 groups was not statistically significant ( p = . 5 ) . Both groups were quite hypertensive, since normal male Wistar rats of the same age have an average blood pressure of approximately 105 mm Hg. Conclusions.These results indicate that in rats under these conditions, presence or ahsence of adrenal tissue has no effect on the severity of hypertension produced by desoxycorticosterone administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1966
1966
1983
1983

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Adsorption could not be demonstrated in strain EA. M. pulmonis strain Ti and M. gallisepticum strongly adsorbed both sheep and guinea pig cells; this supports the findings of other workers (1,24,25). The cat strains CO, Bi, and B2 adsorbed sheep cells only.…”
Section: Methodssupporting
confidence: 90%
“…Adsorption could not be demonstrated in strain EA. M. pulmonis strain Ti and M. gallisepticum strongly adsorbed both sheep and guinea pig cells; this supports the findings of other workers (1,24,25). The cat strains CO, Bi, and B2 adsorbed sheep cells only.…”
Section: Methodssupporting
confidence: 90%
“…Thus, the PG34 strain of the latter haemadsorbed, but the 'Negroni' strain of the same serotype did not. It is interesting that some strains of M. pulmonis haemadsorb, since Berg & Frothingham (1961) reported that tissue culture cells infected with this organism haemadsorbed. Whether colonies of a non-haemadsorbing mycoplasma strain could acquire by continuous passage the ability to haemadsorb or, conversely, whether those of a haemadsorbing mycoplasma could lose this ability is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Probably one of the most confusing properties is the capacity to produce CPE in cells. Other common properties are their filterability through 0.22-nm Millipore membrane filters (117), growth inhibition by specific antiserum (43), sensitivity to chloroform and ether (74), hemagglutination (2), hemadsorption (19,40), resistance to certain antibiotics, morphology by electron microscopy, and ability to induce chromosomal aberrations and morphological changes in infected cells.…”
Section: Cases Of Mistaken Identitymentioning
confidence: 99%